(untitled) (Ghana Journal of Science, Technology and Development, 2021)
This study sought to explore the effects of a twelve week old-decomposed false yam (Icacina oliviformis) tuber on the growth performance of garden eggs (Solanum aethiopicum L.). Freshly harvested false yam tubers were processed and decomposed for twelve weeks. The decomposed tuber was mixed with topsoil in the ratios 1:2, 2:1 (false yam:topsoil ratio (FYTS)); 1:1 (false yam compost:decomposed cow dung ratio (FYCD)); with decomposed tuber (FY-100), and top soil (TS-100) as controls. Garden eggs (test crop) seeds were nursed and transplanted onto each treatment after five weeks. Data were taken on plant growth and productivity parameters. The study revealed that false yam tuber compost is ideal for plant growth and provides a better physical medium to support plant growth when added to topsoil. Results indicated that FYTS (2:1) had the highest plant and leaf area. Also, FYTS (1:2) recorded the highest plant girth and number of leaves. The highest crop yield was recorded from plants grown in topsoil followed by plants grown in the FYTS (1:2) growth medium. Although the study revealed that false yam tuber compost supports plant growth, yield characteristics were not significantly different among treatments. Keywords: Compost; False yam tuber; Icacina oliviformis; Manure; Solanum aethiopicum; Top soil